TYPES AND PROCESS OF RISK MANAGEMENT - alsaadat, khalil (Indonesian Journal of Electrical Engineering and Computer Science, 2021)
The main objective of risk management is not to dampen swings in corporate cash flows or value, but rather to ensure  protection against the possibility of "costly lower-tail outcomes"-situations that would create financial difficulties or make an organization  unable to achieve  its investment plan .This paper discusses  types and  process of risk management and sheds some lights on the importance of this process on  various aspects of human lives ,environment and society organizations .Up on the discussion a risk management model is presented .